Some New Zealand Polyclads (Platyhelminthes, Polycladida) - Holleman, John J. (Zootaxa, 2007)
Eight species of poyclads from New Zealand are presented. Five species were already known to science, and are redescribed. Four of these species have been previously reported from New Zealand, the fifth, Echinoplana celerrima, is new to New Zealand. Two are new species of the genus Chromoplana, Chromoplana sirena n. sp. and Chromoplana kaikouris n. sp. One species belongs to a new genus, Aotearoa ballantinensis n. gen. n. sp. All new species and the new genus are described and discussed. The taxonomic status of Postenterogonia orbicularis, Notoplana suteri with Notoplana australis, and Leptostylochus elongatus is reviewed.